O potrzebie rachunku kosztów w działalności sportowej - Zając, Izabela (Necessity to Keep Cost Accounting in Sports Activity, 2005)
Costs of sports activity form an economic category specific for the operation of an organisation dealing with sport. Traditional solutions for cost accounting adopted in sports organisations are inappropriate with regard to the essence of sports activity costs. The concept of matching costs and revenues in sports organisations is perceived only formally, on the basis of allocation to the accounting period. The lack of cause and effect relation between the mechanism of generating revenues and the mechanism of generating costs results in the situation where it is impossible to consider incurred costs as one factor owing to which revenues are obtained. To secure their existence sports organisations need to have cost accounting meeting the informational requirements in managing the sports organisation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 312-317